Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides